Toward Mechanism-Directed Electrophenotype-Based Treatments for Atrial Fibrillation - Ng, Fu Siong; Handa, Balvinder S.; Li, Xinyang; Peters, Nicholas S. (Frontiers in Physiology, 2020)
Current treatment approaches for persistent atrial fibrillation (AF) have a ceiling of success of around 50%. This is despite 15 years of developing adjunctive ablation strategies in addition to pulmonary vein isolation to target the underlying arrhythmogenic substrate in AF. A major shortcoming of our current approach to AF treatment is its predominantly empirical nature. This has in part been due to a lack of consensus on the mechanisms that sustain human AF. In this article, we review evidence suggesting that the previous debates on AF being either an organised arrhythmia with a focal driver or a disorganised rhythm sustained by multiple wavelets, may prove to be a false dichotomy. Instead, a range of fibrillation electrophenotypes exists along a continuous spectrum, and the predominant mechanism in an individual case is determined by the nature and extent of remodelling of the underlying substrate. We propose moving beyond the current empirical approach to AF treatment, and highlight the need to prescribe AF treatments based on the underlying AF electrophenotype, and review several possible novel mapping algorithms that may be useful in discerning the AF electrophenotype to guide tailored treatments, including Granger Causality mapping.